2019
DOI: 10.1021/acs.est.9b00933
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Polybrominated Diphenyl Ethers (PBDEs) Trends in Top Predator Fish of the Laurentian Great Lakes (GL) from 1979 to 2016: Will Concentrations Continue to Decrease?

Abstract: Polybrominated diphenyl ethers (PBDEs) were widely used as fire retardants and have been detected throughout the Great Lakes (GL) ecosystem. The concentration trends (after fish age normalization) of PBDEs in top predator fish (lake trout and walleye) of the GLs were determined from 1979 to 2016, which includes most of the period when PBDEs were manufactured and used in this region. The fish samples were collected by two national (U.S. and Canada) long-term monitoring and surveillance programs. Trends in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 73 publications
3
36
3
Order By: Relevance
“…In addition to ∑PBDEs, we compared 5 congeners (BDE‐47, ‐99, ‐100, ‐153, and ‐154) that generally have the highest concentrations in aquatic biota (Route et al 2014a; Zhou et al 2019). To estimate study area means, we fit a parametric survival mixed effect model (frailty model; Govindarajulu et al 2011) using the function survreg in package survival for each analyte (Spears and Isanhart 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ∑PBDEs, we compared 5 congeners (BDE‐47, ‐99, ‐100, ‐153, and ‐154) that generally have the highest concentrations in aquatic biota (Route et al 2014a; Zhou et al 2019). To estimate study area means, we fit a parametric survival mixed effect model (frailty model; Govindarajulu et al 2011) using the function survreg in package survival for each analyte (Spears and Isanhart 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Bald eagle nestlings from all study areas had congener profiles that were typical for top-level predators of Midwestern large rivers (Blocksom et al 2010) and the Great Lakes (Gauthier et al 2008;Pérez-Fuentetaja et al 2015;Gandhi et al 2017;Su et al 2017;Zhou et al 2019), although there was substantial variation. We found BDE-47 to be consistently highest, followed by BDEs-99 and -100, whereas BDE-153 and -154 contributed much less across all 12 study areas (Table 1).…”
Section: Congener Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage contribution of BDE-209 to the total PBDE contamination in soil has often been reported to be greater than 60% and may exceed 90%. For example, one detailed investigation of sediments from the Laurentian Great Lakes (GL) showed that BDE-209 was the dominant congener, accounting for more than 90% of the total mass of the five major PBDE congeners present [2]. The accumulated BDE-209 in GL sediments has adversely impacted the GL ecosystem; this is an ongoing problem since BDE-209 is still present in many commercial/industrial products.…”
Section: Introductionmentioning
confidence: 99%
“…Such a system avoided the need to dewater, and allowed for the optimal mixing and control of redox conditions. Importantly, this type of system is ubiquitous in aquatic ecosystems (e.g., wetlands, river/lake/ocean sediments, water reservoirs) and agricultural farms (e.g., paddy field, aquafarm), which are common sinks for the accumulation of POPs/EDCs [ 1 , 2 ]. Moreover, soil slurry reactors (SSRs) are central to many important ad-situ or ex-situ remediation technologies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%